Pertumbuhan Ekonomi dan Pengaruhnya Terhadap Tingkat Kemiskinan di Kota Jayapura - Yundy Hafizrianda; Nurliana (Universitas Cenderawasih, 2024)
This study examines the causal relationship between economic growth and poverty levels in Jayapura City. It focuses on understanding how economic growth affects poverty reduction. Using a linear regression model and statistical tests, such as the t-test and F-test, the research measures economic growth through the Regional Gross Domestic Product (PDRB) and poverty by the number of people living below the poverty line. The findings reveal that economic growth significantly reduces poverty, with a 1% increase in growth leading to a 0.28% decrease in impoverished individuals. Approximately 80.14% of the variation in poverty levels is explained by economic growth. The study recommends that the Jayapura City government implement inclusive growth policies, such as creating quality jobs and promoting micro, small, and medium enterprises (MSMEs), while ensuring that the benefits reach all societal segments, especially vulnerable groups. Further research is suggested to explore additional factors affecting poverty reduction. Key Words : Economic Growth, Poverty, Linear Regression